ANALISIS RISIKO LIKUIDITAS DAN KREDIT TERHADAP KINERJA PROFITABILITAS BANK BUMN - Muhammad Irsyad Nugroho Setiawan (2022)
In banking activities, there is a banking performance that will basically show a picture of the results obtained from the bank's business. This concerns various aspects including finance, marketing, collection, provision of funds, and human resources (HR). In this preparation, we will focus on finance, where there are many components that show indications of banking performance results or also known as financial ratios. Financial ratios will show a situation and condition experienced by banks in the form of percentages, in addition to the proportions there are also criteria that indicate whether or not banks are good at getting results or profits and this time it will focus on state-owned enterprises (BUMN) banking. In determining a bank's profit results, there are several factors that affect the results obtained or also called bank profitability. Through many factors that affect bank profitability, including the ratio of Loan To Deposit Ratio (LDR) and Non-Perfoarming Loan (NPL), namely by analyzing non-performing loans, total loans, and obtaining third party funding sources. All data obtained in the report is through the annual report/annual report of each BUMN.